2013
DOI: 10.1055/s-0033-1345275
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Fertility Preservation for Pre- and Postpubertal Males with Cancer

Abstract: Advances in diagnostic techniques and therapies have drastically improved cancer survival rates. However, the testes are highly susceptible to chemotherapy and radiation therapy, and spermatogenesis and semen parameters can be negatively impacted either permanently or transiently. Fertility preservation is an important issue to patients, and sperm banking has a positive psychological effect that helps patients cope emotionally with cancer. Innovations in sperm freezing and assisted reproductive technologies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…27 Previous studies have suggested that specimens with high sperm concentration, motility, and intact sperm DNA can be stored in relatively large aliquots suitable for intrauterine insemination. 3 On the other hand, specimens with poor sperm motility and higher DNA damage may be stored in multiple small aliquots suitable for further fertility treatment.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Previous studies have suggested that specimens with high sperm concentration, motility, and intact sperm DNA can be stored in relatively large aliquots suitable for intrauterine insemination. 3 On the other hand, specimens with poor sperm motility and higher DNA damage may be stored in multiple small aliquots suitable for further fertility treatment.…”
Section: Commentmentioning
confidence: 99%
“…28,29 Timely cryopreservation is critical because in some cases, >1 visit will be required to cryopreserve sufficient numbers of sperm, or there may be urgent need to start therapy. 27 We have optimized our protocol for the best recovery of healthy sperm and investigated several strategies to further enhance post-thaw recovery of spermatozoa. The limitations of the present study include the following: (1) small sample size, (2) heterogeneity of the population, (3) lack of semen analysis before the overnight shipping of the sample using the NextGen kit, (4) inadequate matched control group, and (5) finally, the patients were counseled over the phone and then asked to review and mail the "Semen Collection and Storage Agreement" by mail.…”
Section: Commentmentioning
confidence: 99%
“…Although penile vibratory stimulation may be effective in some cases, electroejaculation is another option that involves the emission of a mild electrical current from a rectal probe to stimulate ejaculation (Katz et al, 2013;Wang, Muller, & Lin, 2013).…”
Section: Collection Alternativesmentioning
confidence: 99%
“…This impairment is most common in men with testicular cancer, lymphoma, or leukemia (Agarwal & Allamaneni, 2005). Testicular sperm extraction involves the removal of a small amount of testicular tissue by biopsy or aspiration; any sperm found in the tissue are extracted and frozen (Katz et al, 2013;Wang et al, 2013). Reproductive urologists perform these procedures while patients are under anesthesia.…”
Section: Collection Alternativesmentioning
confidence: 99%
See 1 more Smart Citation